(untitled) (Fiep Bulletin - online, 2019)
This article presents how being thrown to the world through your body allows you to incorporate itself as a livedexperience. Linkages and relationships belong directly to their development, because of its permanent presence in life as beingalive; the other (human beings) and the other (the other living beings) are interdependent and are uncorrelated, Consequentlythey are part of the life of each subject. Continuously is evidenced, as, as that person mature and re means for their futureexperiences, their life project takes an important role within their existing; It is there where the presence of the construction of theself, being the result of a consistent network of links and interpretive capacity that leads not only to structure its identity, but to findan educational attitude that will lead him towards his teaching and professional work.